Anticardiolipin antibodies and recurrent spontaneous abortion in Brazilian women - Santana, Natália dos Santos; Spegiorin, Lígia Cosentino Junqueira Franco; Ferreira, Camila Pontes [UNESP]; Vaz Oliani, Denise Cristina Mós; Oliani, Antonio Hélio; Godoy, José Maria Pereira; de Mattos, Cinara de Cássia Brandão; de Mattos, Luiz Carlos (EDIPUCRS, 2015)
AIMS: To determine the frequency of anti-cardiolipin antibodies (aCL) in women with previous history of recurrent spontaneous abortion (RSA). METHODS: Medical records from pregnant women seen from April 2005 to December 2008 at the High-Risk Pregnancy Unit at the Hospital de Base from FUNFARME (Fundação Faculdade Regional de Medicina), in São José do Rio Preto, São Paulo, Brazil, were revised. Patients older than 18 years who had at least two spontaneous abortions and who were tested for aCL were included in the study. Data on maternal age, number of miscarriages and the results of serological tests for aCL were recorded. The exact Fisher's test was used to compare the results. A p value less than 0.05 was considered significant. RESULTS: During the study period a total of 294 pregnant women were seen, from whom 44 consecutive women fulfilled the inclusion criteria. The overall mean age was 33.8±5.4 years (range: 22 to 44; median: 34). Eighteen (40.9%) patients were reagent for aCL and 26 (59.1%) non-reagent, and the difference between their mean age was not statistically significant (reagent: 34.6±5.8 years; non reagent: 33.2±5.2 years, p=0.4001). Fourteen (77.8%) patients presented IgM aCL and six (33.2%), IgG aCL. Two patients (11%) were reagent for both IgM and IgG aCL. In the most of cases the aCL antibody titers were compatible with low risk for pregnancy morbidity. The number of abortions ranged from two to six. The average number of abortions among those reagent for aCL was 3.5±1.1 and in those non-reagent was 2.9±1.1 (p=0.0813). CONCLUSIONS: The frequency of aCL was elevated among patients with a history of RSA, especially those having higher number of fetal losses. Among women with at least two spontaneous abortions, the mean number of abortions was not significantly different between those reagent for aCL and those non reagent.
Keywords: Abortion, spontaneous; Antibodies, anticardiolipin; Antibodies, antiphospholipid; Fetal death; High risk pregnancy; Immunological markers; Miscarriage, recurrent